KEPRAKTISAN BAHAN AJAR BERBASIS KONFLIK KOGNITIF MENGGUNAKAN SOFTWARE TRACKER UNTUK MENGKONSTRUK KONSEP MOMENTUM DAN IMPULS - Fitri, Atikah Dian; Mufit, Fatni (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2022)
The problem of low understanding of concepts in physics learning is still common, including the concepts of momentum and impulse. The use of technology such as Tracker software in building concepts in physics learning is still very lacking. One solution for this problem is to develop physics teaching materials based on cognitive conflicts using tracker software on momentum and impulse materials. This study aims to analyze the practicality of impulse-momentum teaching material products based on cognitive conflicts. This study reported the development stage in the Plomp development model, namely small group evaluation (practicality test). This study's instrument is a questionnaire sheet for practicality tests, which were analyzed by percentage techniques. The results of the practicality test of teaching material products obtained an average percentage of 87.76 with very practical criteria. The cognitive conflict-based impulse momentum teaching materials using tracker software have been practical for students in terms of ease, attractiveness, benefits, and efficiency.